Thiazolium-derivative functionalized silver nanocomposites for suppressing bacterial resistance and eradicating biofilms. (2nd January 2018) - Dai, Xiaomei; Zhao, Yu; Li, Junsheng; Li, Sen; Lei, Ruidong; Chen, Xuelei; Zhang, Xinge; Li, Chaoxing
Abstract : Commercial antibiotic therapies are becoming less efficient due to the emergence of bacterial resistance and the formation of bacterial biofilms. Abstract : Commercial antibiotic therapies are becoming less efficient due to the emergence of bacterial resistance and the formation of bacterial biofilms. The design and development of novel antibacterial agents with efficient anti-biofilm/antibacterial activity and without bacterial resistance is becoming crucial. Herein, a series of poly(5-(2-ethyl acrylate)-4-methylthiazole- g -butyl) functionalized silver nanocomposites (PATA-C4@AgNPs) was synthesized, and their antimicrobial/anti-biofilm activity and biocompatibility were systematically evaluated. The multivalent cationic nanocomposites possessed strong antibacterial activity against both Gram-negative and Gram-positive bacteria without the emergence of bacterial resistance. The PATA-C4@AgNPs were found to disrupt the bacterial membrane and inhibit enzymatic activity. Importantly, these nanocomposites effectively eradicated over 60% of Staphylococcus aureus ( S. aureus ) and Pseudomonas aeruginosa ( P. aeruginosa ) biofilms at a low concentration of 16.7 μg mL −1 . Furthermore, these nanocomposites showed selectivity for eliminating bacteria over human cells, thus avoiding cytotoxicity. The results demonstrated that these simple synthetic nanocomposites have great promise for applications in preventing bacterial infections.